Clinical Treatment of UTI in Rats Induced by Pathogenic E. Coli - Wissam Qadry Mutaab Alqaissy1 , Thaar Mohammed Najim2 , Bahjat Fakhri Mahmood Al-shammari1 , Mustafa (Indian Journal of Forensic Medicine & Toxicology, 2020)
The present study objective was to evaluate the therapeutics effects of ciprofloxacin and gentamicin on UTIinduced experimentally by E. coli in rats. Forty female rats were divided into two groups, infected (30 rats)and control (10 rats). The infected group were inoculated intraurethral by 108suspension of E. coli. Then theinfected group subdivided into 3 subgroups, G1 which serve as control positive, G2 which inoculated by E.coli and then treated by ciprofloxacin 50mg/kg, G3 were inoculated by E. coli then treated with gentamicin40 mg/kg.Treatment with antibiotics started 24 hours after bacterial inoculation and finished 72 hours afterthe initial therapy. The length of antibiotic medication was chosen for both antibiotics as a short-term 3 daystherapy.The animals were monitored for presence of signs. E. coli urine bacterial demonstration were doneat 1 week before infection and 24hrs., 48hrs, 96hrs, 6 days, 12 days and 24 days after infection. There wassignificant increase (P<0.05) in E. coli viable count in all infectedgroups, in addition the result of opticaldensity (OD) by using spectrophotometry record increased threshold of the OD of the urine culture of allinfected groups after (24 hrs.) of infection compared with control group, The current results showed thatUTI symptoms and bacterial isolation were decreased after treatment by both ciprofloxacin and gentamicinas compared with G1 group.In conclusion, ciprofloxacin and gentamicin can alleviate the symptoms of UTI after single dose.